PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP PERILAKU KEWARGAAN ORGANISASI DENGAN MEDIATOR NILAI-NILAI KUALITAS KEHIDUPAN KERJA - Rahmi, Fitria; Riyono, Bagus (Jurnal Psikologi, 2016)
Organizational Citizenship Behavior (OCB) can be formally defined as a discretionary work behaviour of the employees that is not recognized by the formal reward or the sanction system of their organization. OCB can be seen as a voluntary behavior of the employees, which is out of the job description of their obligation, it is not directly related to the formal reward, but useful in improving the efficiency and effectiveness of the organization.Previous research found four aspects of the job characteristic (variety skill, task identity, task significance and autonomy) positively effected on OCB of employee. The objective of this study was to look effect of job characteristic to OCB which mediated by values of Quality of Work Life (QWL). This values as a foundation to display OCB. The subjects of this research were 65 employees from PT. X. Regression analysis showed that job characteristic significant toward OCB through the mediating of QWL values. In another word QWL had a mediator role between job characteristic and OCB. This finding were usefull to improve the OCB in company, with more attention to job characteristic that promote employees’ QWL. The results and benefits of the research were further discussed in the discussion.